The Fyn kinase inhibitor, AZD0530, suppresses mouse alcohol self‐administration and seeking. (7th December 2018) - Morisot, Nadege; Berger, Anthony L.; Phamluong, Khanhky; Cross, Alan; Ron, Dorit
Abstract: Fyn is a member of the Src family of protein tyrosine kinases (PTKs) that plays an important role not only in normal synaptic functions but also in brain pathologies including alcohol use disorder. We previously reported that repeated cycles of binge drinking and withdrawal activate Fyn in the dorsomedial striatum (DMS) of rodents, and that Fyn signaling in the DMS contributes to rat alcohol intake and relapse. Here, we used AZD0530, a CNS penetrable inhibitor of Src PTKs developed for the treatment of Alzheimer disease and cancer and tested its efficacy to suppress alcohol‐dependent molecular and behavioral effects. We show that systemic administration of AZD0530 prevents alcohol‐induced Fyn activation and GluN2B phosphorylation in the DMS of mice. We further report that a single dose of AZD0530 reduces alcohol operant self‐administration and promotes extinction of alcohol self‐administration without altering basal and dopamine D1 receptor‐dependent locomotion. Together, our findings suggest that AZD0530, through its inhibitory actions on Fyn kinase, dampens alcohol seeking and drinking. Abstract : In Morisot et al, we show that systemic administration of the CNS penetrable Fyn kinase inhibitor, AZD0530, attenuates alcohol‐dependent Fyn activation and GluN2B phosphorylation in the mouse dorsomedial striatum. We further report that AZD0530 inhibits operant self‐administration of 20% alcohol. The drug also reduces alcohol seeking and promotes extinction of alcohol self‐administration.